Pengembangan Modul Ajar Berbasis Proyek dengan Pendekatan Culturally Responsive Teaching Topik Ekosistem untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas 5 Sekolah Dasar - Endra Sattrahing Jaya Kusuma; Joko Siswanto; Iin Purnamasari (Journal of Education Reseach and Evaluation, 2025)
Science instruction in schools remains largely theoretical and teacher-centered, resulting in limited student engagement in higher-order thinking processes. Existing instructional modules often provide insufficient opportunities for students to engage in exploration, experimentation, or contextual projects connected to their real-life experiences. This study aims to develop a project-based learning module incorporating a Culturally Responsive Teaching (CRT) approach on the topic of ecosystems to enhance the critical thinking skills of fifth-grade elementary school students. The study employed a Research and Development (R&D) method using the ADDIE model. Validation was conducted by two experts and two practitioners, followed by a small-group trial involving 20 students. Data were collected through observations, tests, interviews, and questionnaires, with data collection instruments consisting of questionnaire sheets. Data analysis was conducted using inferential statistics. The results indicate that the developed module is effective in increasing student engagement and critical thinking skills. Field trial findings show that students became more active in discussions, questioning, and analyzing environmental issues in their surroundings. The module was found to be valid, practical, and effective in improving students’ critical thinking skills. The implications of this study suggest that instructional innovations integrating local cultural contexts into project-based activities can serve as an effective strategy to strengthen science learning in schools. This module not only enriches students’ learning experiences but also provides new directions for teachers in designing more contextual, collaborative, and real-life–relevant instruction.